HRQM and Colliding Gyroscopes: An alternative way of looking at value creation in organizations - Vinkke, Joop; Vonk, Frank (Marketing & Menedzsment, 2019)
How can we look from a different angle at the role and status of HRQM, explicitly integrating “quality” as an added value to HRM-decisions? Focussing upon the added value of the human dimension to strategic decisions in business is a new and slippery road; it is, as HRQM classes at the HAN University have already shown, a road that deserves more attention. In our paper we will explain what the integrative approach towards human resources and quality management does to our students, what the didactics and philosophy behind this approach are and how our students can contribute to the company’s profitability by focussing upon value creation within a systemic account of performance, gyroscopic thinking and internally motivated contributions to strategic decisions.